PENERAPAN METODE CAMEL (CAPITAL, ASSET, MANAJEMEN, EARNING DAN LIQUIDITY DALAM MENGANALISIS TINGKAT KESEHATAN BANK SYARIAH) KABUPATEN KOLAKA - Andi Nasrah Ningsih (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
This study aims to explain and analyze the CAMEL method (Capital, Asset, Management,Earning liquidity) in the health level of Islamic banks in Kolaka district, especially inknowing the HEALTHY and NOT HEALTHY a bank is in Kolaka Regency.The type ofresearch used Descriptive Research is analyzing data through secondary data whether in theform of media, journals, websites or information taken from the bank concerned, for exampleyear-end documents, this research uses a qualitative approach to Islamic banks, namely byanalyzing data -the financial statement data to determine the category of the bankingcompany can be related to healthy or unhealthy.The results showed that using the CAMELmethod in analyzing the health of the Bank in 2018 showed that BNI Syariah was categorizedas HEALTHY, in contrast to Bank Mualamat Indonesia which was categorized as NOTHEALTHY.